A Determinant Expression for the Generalized Bessel Polynomials - Sheng-liang Yang; Sai-nan Zheng (Journal of Applied Mathematics)
Using the exponential Riordan arrays, we show that a variation of the generalized Bessel polynomial sequence is of Sheffer type, and we obtain a determinant formula for the generalized Bessel polynomials. As a result, the Bessel polynomial is represented as determinant the entries of which involve Catalan numbers.